The influence of particle size in adjuvant induced innate and adaptive immune responses - Hearnden, Claire (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Advances in vaccine development have enabled the application of adjuvanted subunit vaccines as opposed to attenuated or killed whole organisms. However the efficacy of this approach is strongly dependent on the optimisation of adjuvant characteristics. Biodegradable particles are potent adjuvants that have the capacity to elicit strong and long-lasting immunity to associated antigens. Although the optimum size of these particles for generating humoral responses has been investigated, how particle size dictates adjuvant induced innate immunity and T cell responses is unclear.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin